Catastrophes dites naturelles, risques et développement durable : Utilisations géographiques de la courbe de Farmer - Patrick Pigeon (VertigO)
This paper aims at justifying how the well-known Farmer’s curve may be used as a means to formalize relationships between risks, so-called natural disasters and sustainable development. It may help geographers to clarify these relationships relying on mainly post-disasters field survey experiences. We find that sustainable development cannot be challenged by the increasing disaster frequencies main databases display, such as EM-DAT. Policies wishing to strengthen local societies resilience, and aiming at reducing the intensities of damages for the next events, seem to be consistent with the fundamentals of sustainable development. At the same time, they produce unwanted and not fully predictable effects geographers find back during field surveys. This is consistent with the fact that farmer’s curve may be considered a means to identify complexity.